Lithium‐Ion Batteries: Super‐Aligned Carbon Nanotube Films as Current Collectors for Lightweight and Flexible Lithium Ion Batteries (Adv. Funct. Mater. 7/2013). (11th February 2013) - Wang, Ke; Luo, Shu; Wu, Yang; He, Xingfeng; Zhao, Fei; Wang, Jiaping; Jiang, Kaili; Fan, Shoushan
<x xml:space="preserve">Abstract</x> On page 846, Jiaping Wang and co‐workers report carbon nanotube (CNT) current collectors for lithium ion batteries (LIBs). The CNT current collectors with excellent flexibility, extremely low density, and tunable thickness are fabricated by cross‐stacking continuous CNT films drawn from super‐aligned CNT arrays. Electrodes with CNT current collectors show better wetting, stronger adhesion, lower contact resistance, greater mechanical durability, and higher energy density than those with metal current collectors, suggesting CNT films as a promising type of current collector for lightweight and flexible LIBs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>